Strategi Pengembangan Kawasan Peternakan Sapi Potong Berbasis Sumberdaya Lokal di Kabupaten Solok Selatan - S. Octarini; J. Hellyward; F. Madarisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to analyze the potential, carrying capacity of local resources and strategies for developing beef cattle farming areas. This research was conducted in seven sub-districts in South Solok Regency on the basis of this area as a local cattle center in West Sumatra and the flagship program "one family one cow." The determination of informants was carried out purposively, consisting of: 1 worker, 1 livestock extension staff and 2 breeders. Data analysis with Location Quotient Analysis, Internal and External Environment and SWOT. The results showed that the physical environment of South Solok Regency was suitable for the development of beef cattle farming (LQ > 1). The factors that influence the development of beef cattle area are internal strengths consisting of agro-climatic support, the entrepreneurial spirit of breeders, the potential availability of animal feed (IDD 10.3 and KPPTR 101.401 ST) and the large potential availability of agricultural waste and industrial waste. Meanwhile, the internal weakness is: the low budget for agricultural development and the region is not equipped with a telecommunications network. External opportunities are the potential and carrying capacity of the policy. Meanwhile, the threat factor with the highest score is natural error, where this area is prone to natural disasters. An alternative strategy for developing beef cattle business is optimizing the use of forage and improving the quality of human resources to support production efficiency.